EFFECT OF CIVIL WAR ON THE PERFOMANCE OF TOURISM INDUSTRY IN AFRICA .A CRITICAL LITERATURE REVIEW - Kimani, James (International Journal of Modern Hospitality and Tourism, 2021)
Purpose: The tourism industry is playing an increasingly important role in the global economy, contributing 5 percent of gross domestic product (GDP), 30 percent of service exports, and 235 million jobs. The general objective of the study was to examine effect of civil war on the performance of tourism industry in Africa. Methodology: The paper used a desk study review methodology where relevant empirical literature was reviewed to identify main themes and to extract knowledge gaps. Findings: The study concluded tourists will not travel to countries or areas within large countries where they feel threatened. Some relatively recent examples are the 11 September 2001 events in the United States, the bombing in Bali on 12 October 2002 and the Iraq war of March 2003 (and ongoing). When such events occur, there is an immediate and often massive dislocation to country and regional travel affecting performance of Africa Tourism Recommendations: The study recommends that tourism managers should focus on the value of their product to be competitive in the international market. Tourism managers in Africa should garnering strong political support for tourism at a high level in government. The study recommends that tourism managers should focus on the value of their product to be competitive in the international market. Tourism managers in Africa should garnering strong political support for tourism at a high level in government